Effect of acidulant addition on yogurt fermentation - Schmidt, Karen A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Yogurt was manufactured by pre-acidifying the yogurt mix with citric acid, lactic acid, or concentrated lemon juice either before or after pasteurization to a target pH of 6.2, and then the traditional manufacturing process was continued. Adding citric acid or lemon juice to the yogurt mix after pasteurization resulted in a 13% reduction in fermentation time compared with the control. This reduction in fermentation time may result in greater efficiency for yogurt manufacturers, allowing for a more sustainable manufacturing process.
Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Dairy; Dairy processing; Citric acid; Lemon juice; Yogurt